2015
DOI: 10.1016/j.ejca.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Randomised phase III trial of second-line irinotecan plus cisplatin versus irinotecan alone in patients with advanced gastric cancer refractory to S-1 monotherapy: TRICS trial

Abstract: No survival benefit was observed upon adding CDDP to CPT-11 after S-1 monotherapy failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
2
27
2
Order By: Relevance
“…In terms of confirmed ORR, which is similar to the addition of cisplatin to docetaxel, the addition of S-1 to docetaxel showed a very low ORR and did not show any significant difference compared to docetaxel alone (4.3% in the D arm, 4.3% in the DC arm, and 8.7% in the DS arm; p > 0.990). Previous studies of second-line chemotherapy in MGC showed an ORR ranging from 0% to 22% [8,9,[24][25][26][27], and the ORR of the present study was much lower than the ORRs of previous studies. The small sample size might have affected the result because the baseline characteristics and treatment delivery did not appear to differ from previous studies.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In terms of confirmed ORR, which is similar to the addition of cisplatin to docetaxel, the addition of S-1 to docetaxel showed a very low ORR and did not show any significant difference compared to docetaxel alone (4.3% in the D arm, 4.3% in the DC arm, and 8.7% in the DS arm; p > 0.990). Previous studies of second-line chemotherapy in MGC showed an ORR ranging from 0% to 22% [8,9,[24][25][26][27], and the ORR of the present study was much lower than the ORRs of previous studies. The small sample size might have affected the result because the baseline characteristics and treatment delivery did not appear to differ from previous studies.…”
Section: Discussioncontrasting
confidence: 80%
“…In a phase III study (TCOG GI-0801/BIRIP) that compared irinotecan alone with irinotecan plus cisplatin in patients with metastatic or recurrent gastric cancer refractory to S-1-based first-line chemotherapy, the PFS (3.8 months vs. 2.8 months; hazard ratio [HR], 0.68; p=0.0398) and the DCR (75% vs. 54%, p=0.0162) were significantly better in the irinotecan plus cisplatin group than in the irinotecan alone group, whereas there was no difference in survival between the two groups [25]. In another phase III trial (TRICS), which also compared irinotecan alone with irinotecan plus cisplatin in advanced gastric cancer refractory to first-line S-1 monotherapy, the addition of cisplatin to irinotecan did not improve the PFS (4.6 months vs. 4.1 months; HR, 0.860; p=0.376) or OS (13.9 months vs. 12.7 months; HR, 0.834; p=0.288) compared to irinotecan monotherapy [26].…”
Section: Discussionmentioning
confidence: 99%
“…We selected two studies, the TRICS trial 18) and the TCOG GI-0801/BIRIP trial 17) . We selected these two trials because they were randomized phase III trials employing the same regimen of biweekly CPT-11 plus CDDP versus CPT-11 alone in a second-line setting for advanced or recurrent gastric cancer.…”
Section: Selection Of the Studiesmentioning
confidence: 99%
“…Recently, two randomized trials employing the same regimen of biweekly CPT-11 plus CDDP versus CPT-11 alone in the second-line setting have been reported 17,18) . Higuchi et al reported (n = 130) that biweekly CPT-11 plus CDDP significantly prolonged progression free survival (PFS) (HR: 0.68) compared with CPT-11 alone, but did not demonstrate an overall survival (OS) benefit (HR: 1.00) in patients with metastatic or recurrent gastric cancer that progressed after S-1-based first-line chemotherapy 17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation